Enhancing Early Literacy and Disaster Preparedness through an Interactive Educational 3D Pop-Up Book Snakes and Ladders Game with Barcode - Angelina Marta Hakim; Ali Formen (Jurnal Pendidikan Anak Usia Dini Undiksha, 2025)
Low early literacy levels and limited disaster preparedness education among young children highlight the need for innovative and developmentally appropriate learning media. This study aims to analyze the effectiveness of a 3D Pop-Up Book–based Snakes and Ladders game with barcode features in improving early literacy and disaster preparedness among children aged 5–6 years. The study employed a quantitative approach with a pre-experimental One-Group Pretest–Posttest design. The participants consisted of 16 children aged 5–6 years who took part in play-based learning activities. Data were collected using a four-point Likert scale questionnaire administered before and after the intervention. The research instrument measured two main aspects: early literacy skills and disaster preparedness understanding. Data analysis was conducted using a paired sample t-test complemented by effect size analysis to determine the magnitude of the intervention’s impact. The results indicate that the use of the educational game significantly improved children’s early literacy skills and their understanding of disaster preparedness. In addition, children demonstrated high levels of enthusiasm and active engagement during the play-based learning process. The findings indicate that a 3D Pop-Up Book–based educational game with barcode features is an effective, engaging, and meaningful learning medium for early childhood education. The study highlights the importance of developing interactive game-based learning media to enhance literacy while fostering contextual and enjoyable disaster mitigation awareness from an early age.